Norway maple displays greater seasonal growth and phenotypic plasticity to light than native sugar maple (2012)
Norway maple (Acer platanoides L), which is among the most invasive tree species in forests of eastern North America, is associated with reduced regeneration of the related native species, sugar maple (Acer saccharum Marsh) and other native flora. To identify traits conferring an advantage to Norway maple, we grew both species through an entire growing season under simulated light regimes mimicking a closed forest understorey vs. a canopy disturbance (gap). Dynamic shade-houses providing a succession of high-intensity direct-light events between longer periods of low, diffuse light were used to simulate the light regimes. We assessed seedling height growth three times in the season, as well as stem diameter, maximum photosynthetic capacity, biomass allocation above- and below-ground, seasonal phenology and phenotypic plasticity. Given the north European provenance of Norway maple, we also investigated the possibility that its growth in North America might be increased by delayed fall senescence. We found that Norway maple had significantly greater photosynthetic capacity in both light regimes and grew larger in stem diameter than sugar maple. The differences in below- and above-ground biomass, stem diameter, height and maximum photosynthesis were especially important in the simulated gap where Norway maple continued extension growth during the late fall. In the gap regime sugar maple had a significantly higher root shoot ratio that could confer an advantage in the deepest shade of closed understorey and under water stress or browsing pressure. Norway maple is especially invasive following canopy disturbance where the opposite (low root shoot ratio) could confer a competitive advantage. Considering the effects of global change in extending the potential growing season, we anticipate that the invasiveness of Norway maple will increase in the future. © 2012 The Author. Published by Oxford University Press. All rights reserved.